Prediction of anxiety and depression among the transgender in Bangladesh - Easha, Ishrat Jahan; Faiza, Fairooz Afnad; Sadique, Mohammad Rafiuddin; Tabassum, Fatima; Uddin, Md. Rakib (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.